(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2020)
This paper is carried out in the coastal area of Bahía Creek and its surroundings, highlighting 15 km to the west Caleta de los Loros. This area is located on the coast of Río Negro province, which is part of the San Matías gulf. Bahía Creek is located precisely at 41º 05´S, 63º 56´ W. It belongs to the department of Adolfo Alsina and it is located 70 km SW of Viedma city, capital of the province and 70 km E of San Antonio Oeste port (Fig. 1). The main objective of this work is a morphological classification of the dunes present in the dunefield of Bahía Creek, based on the proposed classifications by McKee (1979), Lancaster (1995), Hesp (2011) and Sanjaume and Gracia (2011). For this it is necessary to observe satellite images and aerial and field photographs, together with the study of wind data. With this information it is also possible to know the factors that can condition the location of the dunes, their migration, their mobility index according to Lancaster (1988) and the sand drift potential (DP), the resulting drift direction (RDD), the resulting drift potential (RDP) and the directional variability of the wind through the RDP/DP relationship through the methodology proposed by Fryberger (1979). The used material consisted of aerial photographs from 1986 from the Servicio Geológico Minero Argentino, scale 1:80.000; the digital elevation model (DEM) of the ALOS satellite and Landsat 8 images from 2017, the latter of 30 m of spatial resolution. The images available in Google Earth, Earth Engine and Bing Maps were also used. The wind data used correspond to the records of the Servicio Meteorológico Nacional weather stations located in the towns of Viedma and San Antonio Oeste (SAO). Within these winds, those capable of mobilizing the material available in the study area (effective wind), of an average grain size of 0.25 mm (Toffani, 2018), are those that reach speeds equal to or greater than 6.7 m/s. This value was calculated using the equations proposed by Bagnold (1954). The effective wind was recorded in 34% of the total measurements within Viedma and SAO stations. In Viedma (Fig. 2) the main effective wind directions are NW (13.9%), and SW (10.1%), while in SAO (Fig. 2) the NW direction (18.8%) also predominates, followed by WNW (10.4%). These values suggest that the net displacement of the dunes occurs from NW/SW to SE/NE. Subsequently, applying the mobility index, it was obtained that the dunes, on average, correspond to active except in the interdune, with a value of 124. The annual value of DP is 1090, the RDP 392 and the annual RDD direction is 76 o, indicating a displacement of the sediments towards the ENE (Fig. 3). The directional variability of the wind regime, characterized by the RDP/DP ratio, shows the value of 0.36. This means that Bahía Creek is located within a high energy environment, with a wind regime between complex and bimodal. The annual rate of migration for the dunes studied, which are located within fields of dunes 2, 5 and 7, between 1986 and 2017 was 6.02 ± 0.3 m/year (Fig. 4), towards NE – SE. The dunefield is transgressive and is characterized by a gentle relief that goes from 0 to 60 – 90 meters above sea level from the beach towards N and E. The active dunes rest on a field of stabilized dunes and this in turn is located on an old dissected alluvial plain. The dunes can reach a relative height of 16 m and are composed of medium to fine sands, generally very well sorted, with the exception of some well sorted. Within the classification itself (Fig. 5), the dune fields 1 (Fig. 6a), 3 (Fig. 6c), 5 (Fig. 8a) and 6 (Fig. 8b) are characterized by the predominance of crescentic dunes. Field 2 has mainly linear and reversible crest dunes (Fig. 6b). Field 4 is characterized by star dunes (Fig. 6d). Field 7 is composed of symmetric, asymmetric and lateral coalescence parabolic dunes (Fig. 8c – d). While field 8 is represented by embryonic dunes (Fig. 9a – b), field 9 by climbing dunes (Fig. 9c) and field 10 by hanging dunes (Fig. 9d). Echo dunes (Fig. 10a), falling dunes from the cliff (Fig. 10b) and enveloping dunes (Fig. 10c) were also recorded in the field. In addition, within the different sectors mentioned, the formation of nebkas occurs (Fig. 10d). The wavelengths vary between 30 m and 350 m, the lowest values are after the creek, that is where the dunefield begins, and in the most distal part, east of the dune field 6. This sector is also the one that records the highest values. This distribution is coherent, since the first accumulations are of smaller size and close to each other, in general they are growing and having greater wavelength, until reaching a maximum. Where transport begins to decrease they acquire smaller sizes. The greatest lengths, up to 1 km, due to the development of its arms, are reached by the parabolic dunes. The smallest, 10 m, are those presented by the barchans. Regarding the width, the latter are also those that have smaller sizes, 10 m, while the largest correspond to coalescent parabolic dunes and transverse or barchanoid ridges, which are between 500 m and 600 m. It is also observed that the larger the size of the dunes in terms of length and width, the wavelength is greater. Variations in wind and sand transport rate at different time and space scales appear to be the most important control of their size and spacing. These factors, together with vegetation, humidity, input of sand, topography and constructions or anthropogenic processes, influence the distribution of the active dunes and at the same time in the location of the different types of dunes. The most relevant for the population of Bahía Creek are the constructions that act as an obstacle to the transport of sediments by the wind. They difficult the passage of winds coming mainly from the S, which contribute to the movement of the dunes towards the NE, leaving them more relative weight to the winds of the W and the NW. The latter cause the fastest advance of the dunes towards the E and SE, that is, where the buildings are. Bahía Creek dunefield, due the types of dunes and their distribution, shows great complexity, mainly due to the variations in the effective winds, and that over time generate compound and complex dunes. In Argentina, coastal dunefields with similar characteristics are develop, for example, around San Antonio Oeste and Este, in Río Negro province (Carbone et al., 2007); in the south and east of Buenos Aires province (Barrera Medanosa Austral y Oriental) (Bértola and Cortizo, 2005; Cortizo and Isla, 2007, 2012; Bértola et al., 2009); and in Península Valdés, Chubut province (del Valle et al., 2008). However, Bahía Creek has exceptional characteristics due to the possibility that offers to appreciate a natural environment with different geomorphological features with virtually no anthropic disturbance. Among these are beaches, cliffs and mainly the vast dunefield, which enters the continent with a concentration and striking diversity of dunes. It is a site that is not yet highly exploited by urbanization and tourism and allows visitors to access an almost virgin and pristine environment, which includes Caleta de los Loros, Pozo Salado and Punta Mejillón Protected Area. This last one is conformed to a greater extent by a tidal plain, which added to the rest of the coastal environment and to the dunefield, makes the area have a great diversity of species. In addition, the importance of the study of the dunefield lies in its proximity to the seaside town of Bahía Creek, which acquires more visitors over the years and is affected by the migration of the dunes, which sometimes have already covered houses or arrived at a distance very close to them and continue to move in that direction.